The pottery - Sheridan, Alison; McGill, Catherine; Sheridan, Alison; Lawson, John; McGill, Catherine; Dean, Valerie (Scottish Archaeological Internet Reports, 2006)
Specialist reports on the pottery which includes material of Neolithic, Beaker, Bronze Age, Iron Age, post-Roman and post-medieval date.